Logística en la transportación de agroquímicos en la empresa Aerovic C.L Zona San Juan, Del Cantón Puebloviejo. - García Flores, María Emilia (2022)
Transportation and supply logistics is a relevant process in the commercial management of companies that buy and sell products, because it influences the development of operational activities and the satisfaction of the needs of the consumer market. Therefore, the supply chain allows the fulfillment of commercial objectives; for this reason, the objective of this case study is based on analyzing the supply and transportation logistics of the company Aerovic C.L. to establish the main causes and consequences that generate supply problems in the organization. The methodology is composed of the application of the empirical method, since the main research findings are analyzed through the experiences and information obtained in the research process, the types of field and documentary research were also applied, while the technique used was the interview, which allowed obtaining relevant information regarding the transportation logistics of the company studied. The results of the study revealed that in the company Aerovic C.L. there are problems related to the lack of inventory of agrochemical products necessary for the aerial fumigation of banana plantations, which has caused discomfort and dissatisfaction of the consumer market due to the lack of timely attention to the needs of customers. Also, internal weaknesses were determined with respect to the transportation logistics that make it impossible for the products or inputs to be promptly in the warehouses of the operation centers of the company analyzed.